Blended binder system with Incinerated Paper Ash (IPA) for Solidification/Stabilization (S/S) - Mat Zin, Mazni; Zafyrah Mohd Zahid, Azyan; Khalid, Noorashiekin; Zalikha Saifullizam, Nadia; Syarizawani Wan Chik, Wan; Farahin Kamaruddin, Siti; Shahidah Sharipudin, Siti; Mayuze, Nor; Johan Ibrahim, Mohd; Jumali, Saiful; Ain Umaiban Yusof, Nurul (International Journal of Engineering and Technology, 2018)
This research explored the potential to use IPA as a binder for the treatment of industrial waste sludge. Within the study, Incinerated Paper Ash (IPA) was used together Ordinary Portland Cement (OPC), a main material employed in solidification/stabilization (S/S) methodology to treated industrial ceramic sludge. The issues created by OPC in sustain the surroundings and cost force the new material must replace OPC as binder within the treatment methodology. The impact of the various IPA compositions within the system has been examined. The Unconfined Compressive Strength (UCS) and Toxicity Characteristic Leaching Procedure (TCLP) were used to assess the viability of IPA in sludge treatment once 28 days. The great result of compressive strength and decrease in heavy metals shows the potential of IPA in OPC replacement.Â Â Â